Establishment of a metric to characterize retroreflector properties using a consumer-grade colour camera. Issue 1 (21st December 2022) - He, Huayang; Su, Wenying; Cheng, Qiutong
Abstract: The coefficients of retroreflection and chromaticity coordinates are critical metrics for determining the quality of a retroreflector. However, conventional retroreflection measurement techniques rely heavily on the night-time colour, size and characteristics of the sample being measured. This complicates the measurement process and leads to deviations in the test results. In addition, chromaticity cannot be determined using this approach. Therefore, it is necessary to improve the measurement accuracy, simplify the measurement process and achieve the measurement of the traffic sign R A and chromaticity coordinates simultaneously. In this study, an improved method for retroreflector characterization using imaging was proposed. This allowed for the measurement of the coefficients of retroreflection and the chromaticity coordinates simultaneously, and only a white standard sample was required for calibration. The primary components of the proposed system included a lighting projector, a receiver, two motorized rotational stages, a retroreflective sample holder and customized software that using scaling factors to convert a digital signal into sample retroreflection coefficients and retroreflective chromaticity coordinates. The experimental results indicated that the raw data output from the camera exhibited a positive correlation relationship with the luminous flux from the surface of the retroreflector. The maximum measurement errors for the retroreflection and chromaticity were −12.2 cd/(lx·m 2 ) and −2.09%, respectively. This method was inexpensive and convenient, used a commercially available digital camera, could help to identify defects in retroreflection and chromaticity for retroreflective sheeting and led to increased accessibility for the quality control of retroreflective sheeting.